Que pode o blog? desmontando os fetiches com uma leitura política - Silva, Márcia Virgínia Mignac da (2012)
The "blog explosion" is intensified in the 90 s decade, and won enormous range. In Brazil, this reached an estimated 3 or 7 million blogs and 12.3 million users. There is, at the same time, another expansion: the collective forms of grouping those were becoming increasingly popular in our country. This research began of a proposal for linking the two phenomena, and makes it the context of this research. Blogs were welcomed as democratizing spaces of visibility - premise here challenged, with the hypothesis that happened just the reverse of what was described. Even at the height of its popularity, blogs operated as tools to aggregation and location, and not as devices for horizontal distribution of information and very broad. The association held recently between blogs and social networks (Facebook, Twitter ...) indicates that direction. The problem that lead the research claim that the readings that have become popular blog about the impacts of widespread fetishes that have staining the identification of the type of visibility and sociability, in fact, was produced by them. Then discuss this meant a phenomenon occurring only, or whether it also extends to new forms of online communication. The object of this research is how four collective use their blogs and their effects on the constitution of the groups themselves. Were selected groups that located in regions of entirely different characteristics: the creative core of Dirceu (Teresina, Piauí), O 12 (Votorantim, São Paulo), Dimenti (Salvador, Bahia) and Cauliflower Mincomunidade World (Curitiba, Paraná), and also the blogs of artists Dani Lima (Rio de Janeiro, RJ) and Thelma Bonavita (São Paulo, SP). The theoretical research focuses political relations between media, power, and collective body, especially the contribution of authors such as Kerckhove (2009), Lemos (2003, 2009), Recuero (2003a, 2003b), Primo (2008a, 2008b ) Katz and Greiner (2001, 2005), Santos (2003), Agamben (2009), Lipovetsky (2005), Santos ( 2009), Zizek (1996) and McNeill (1995). The methodological approach combines literature review, field research through application of semi-structured interviews and analysis of examples that constitute the corpus of the research